Physical fitness analysis of elementary school students: a study to design an exercise program - Hardinata, Riyan; Rinto, Rinto; Deski, Deski; Hartikasari, Hartikasari; Nofita, Tika; Hendra, Hendra; Pardi, Pardi; Cadiente, Derick Sam A. (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. Physical fitness is a parameter used to assess a person's ability to perform physical activities, lead a productive life and have good health. The body's ability to overcome fatigue during sports activities is very important to maintain concentration and focus on learning. Therefore, information about the physical fitness of elementary school students is very important to know.Material and Methods. This research method uses a quantitative approach conducted by survey then giving tests and measurements to elementary school students. The sampling technique uses total sampling, so all students in one class are sampled, totaling 25 people. This research instrument uses the 12-Minute Cooper Test. Analysis is assisted using the SPSS 26 application.Results. Based on these results, it shows that physical fitness, especially the endurance of elementary school students, is included in the moderate interpretation with a percentage of 52%. Based on the results of research on the analysis of physical fitness, especially aerobic endurance in elementary school students, it can be concluded that students' physical fitness is still in moderate interpretation.Conclusion. The results of this study serve as a reference for designing lessons to improve physical fitness. That way these results can be taken into consideration in developing exercise programs to improve the physical fitness of elementary school students.